Current status of next-generation vaccines against mpox virus: a scoping review - Bravo-Vázquez, Luis Alberto; Bernal-Vázquez, Daniela; Duttaroy, Asim K.; Paul, Sujay (Frontiers in Pharmacology, 2025)
IntroductionThe mpox disease, caused by the mpox virus (MPXV), has become a rising public health issue due to its potential to cause outbreaks. Consistently, this investigation aims to evaluate the current advances in the development of novel immunotherapeutic approaches against MPXV, which are crucial for preventing and controlling mpox spread.MethodsThis scoping review was performed by analyzing the content of English-language articles published between 2018 and 2024, which reported the development of next-generation vaccines against MPXV and their assessment in animal models. Patents within the scope of this research were also included. Contrarywise, studies based solely on immunoinformatic methods, reviews, book chapters, news, and others were excluded. The literature search was executed in 11 databases, such as Scopus, MEDLINE, and PubMed.ResultsA total of 36 records (32 studies and 4 patents) were included in this review. All 32 articles contain preclinical studies with varied group sizes (4–16) in which the main animal models were BALB/c mice. Less commonly used models included CAST/Ei mice and cynomolgus macaques. Moreover, most vaccines targeted one or more MPXV antigens, such as A29L, A35R, B6R, and M1R, through active immunization (via mRNAs or recombinant antigens) or passive immunization (antibody delivery).ConclusionOverall, new generation vaccines might represent prospective candidates to combat the mpox health concern. Nonetheless, several of the analyzed studies possess drawbacks, including animal models with limited similarity to humans, small group sizes, and brief follow-up durations. Consequently, additional research is required to ascertain the long-term protection, efficacy, and safety of these immunotherapeutic approaches.